Delays in subsidy payments from the common agriculture policy of the European Union - Gauffin, Kerstin (2020)
This Master's thesis is about how some farmers in Uppsala County experience delays in subsidy payments from the Swedish Board of Agriculture (SBA). This topic falls within the field of rural development as farms are in rural areas and are essential for society as they provide food and other agricultural goods. As farms are essential, it is important that the SBA is efficient. The research material consists of qualitative interviews of ruminant farmers in Uppsala County and a literature review of how the rural development programme (RDP) is designed and evaluated. This study shows that farmers experience delays in subsidy payments from the SBA similarly but how they cope with the delays varies.